Proceedings of the 30th ACM SIGSOFT International Symposium on Software Testing and Analysis 2021
DOI: 10.1145/3460319.3464801
|View full text |Cite
|
Sign up to set email alerts
|

Exposing previously undetectable faults in deep neural networks

Abstract: Existing methods for testing DNNs solve the oracle problem by constraining the raw features (e.g. image pixel values) to be within a small distance of a dataset example for which the desired DNN output is known. But this limits the kinds of faults these approaches are able to detect. In this paper, we introduce a novel DNN testing method that is able to find faults in DNNs that other methods cannot. The crux is that, by leveraging generative machine learning, we can generate fresh test inputs that vary in thei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For example, when testing Deep Neural Networks (DNNs) that recognise handwritten digits in greyscale images, two dimensions of interest may be the boldness and discontinuity of the handwriting stroke (see section 2). In this case, DEEPHYPERION-CS uses the misclassification distance as fitness function [12,59,18] to generate greyscale images containing digits written using strokes with different boldness and discontinuity (see Figure 1). The misclassification distance is computed as the difference between the activation value of the neuron associated with the correct label and the highest incorrect activation from the DNN's softmax layer output (hence, it becomes negative as a misclassification occurs).…”
Section: Guiding Illumination Search With Contribution Scorementioning
confidence: 99%
See 1 more Smart Citation
“…For example, when testing Deep Neural Networks (DNNs) that recognise handwritten digits in greyscale images, two dimensions of interest may be the boldness and discontinuity of the handwriting stroke (see section 2). In this case, DEEPHYPERION-CS uses the misclassification distance as fitness function [12,59,18] to generate greyscale images containing digits written using strokes with different boldness and discontinuity (see Figure 1). The misclassification distance is computed as the difference between the activation value of the neuron associated with the correct label and the highest incorrect activation from the DNN's softmax layer output (hence, it becomes negative as a misclassification occurs).…”
Section: Guiding Illumination Search With Contribution Scorementioning
confidence: 99%
“…However, they are not focused on generating inputs with different structural features and, thus, covering the feature map. Another alternative for input generation are generative ML approaches that approximate the input distribution, such as Variational Auto-Encoders (VAEs) [37] and Generative Adversarial Networks (GANs) [18]. VAEs and GANs are very useful when a model of the inputs is not available, e.g., real-world images from ImageNet.…”
Section: Deephyperion-cs Is a Model-based Test Input Generation Techn...mentioning
confidence: 99%
“…Among the seven possibilities tried, the authors found o to be more effective in the formulation present in Equation 2. 16, where Z(x) represents the output of the target classifier f except the last softmax layer and j and j are the indices of y and y target , respectively. By incorporating the constraint in the objective function, the optimization problem becomes minimizing Equation 2.17, where c is a suitable positive constant and D one of the L 0 , L 2 , and L ∞ norms.…”
Section: Adversarial Attacksmentioning
confidence: 99%
“…In the DNN test input generators (TIG) literature [2], [14], [19], [20], [30], [31], with just one notable preprint as an exception [18], we are not aware of any paper aiming to generate true ambiguity directly, while most TIG aim for other objectives. Some works [19], [20], [32] propose to corrupt nominal input in predefined, natural and labelpreserving ways to generate OOD test data.…”
Section: Related Workmentioning
confidence: 99%
“…Autoencoders (AEs) are a powerful tool, used in a range of TIG [18], [27], [28], [31]. AEs follow an encoder-decoder architecture as shown in the blue part of Figure 2: An encoder E compresses an input into a smaller latent space (LS), and the decoder D then attempts to reconstruct x from the LS.…”
Section: A Interpolation In Autoencodersmentioning
confidence: 99%